Kajian Proses Bisnis Komoditas Ekspor Ikan Kakap Merah (Studi Kasus PT. TOFICO PPS Kota Kendari) - Fitriani, Rahma; La Onu, La Ola; Yusuf, Sarini; Mansyur, Akhmad; Risfandi (Universitas Halu Oleo, 2023)
This study aims to assess the the demand of PT. Holi Osean Indonesia and the readiness of PT. Tofico as a seller of red snapper. Also, business processes starting from planning to buying and selling transactions between PT. Tofico as a seller in Indonesia and PT. Holi Osean Indonesia as a buyer in China was reviewed. Research conducted at PT. Tofico Ocean Fisheries Port (PPS) Kendari City in June 2022. Data obtained through observation, interviews and documentation. The data analysis used was descriptive qualitative analysis. The study showed that the demand for red snapper commodity at PT. Holi Osean Indonesia in China to PT. Tofico in Indonesia every month was 3.250 kg/month and can be fulfilled by PT. Tofico. The export business process started from PT. Tofico in Indonesia prepared red snapper commodities based on the quality standard of PT. Holi Osean Indonesia. Frozen red snapper then would be sent to China via the Kendari new port container operated by PT. Tanto. The shipping insurance was paid to ensure the safety of the commodity at the Chinese port. PT. Holi Osean Indonesiab then picked up the commodity in question at the Chinese port to be delivered and marketed in China.